Biosynthesis of Monoterpenes and Norisoprenoids in Raspberry Fruits (Rubus idaeus L.): The Role of Cytosolic Mevalonate and Plastidial Methylerythritol Phosphate Pathway - Hampel, Daniela; Swatski, Anna; Mosandl, Armin; Wüst, Matthias (Journal of agricultural and food chemistry, 2007)
The biosynthesis of the monoterpenes (−)-α-pinene, linalool, and the norisoprenoids α- and β-ionone in raspberry fruits (rubus idaeus L.) was investigated by in vivo feeding experiments with [5,5-2H2]-mevalonic acid lactone and [5,5-2H2]-1-deoxy-D-xylulose. The volatile compounds were extracted by stirbar sorptive extraction and analyzed using thermal desorption-multidimensional gas chromatography–mass spectrometry (TD-enantio-MDGC-MS). The feeding experiments demonstrate that (−)-α-pinene and (S)-linalool are exclusively synthesized via the cytosolic mevalonic acid pathway. In contrast, 2H-labeled (R)-(E)-α-ionone and 2H-labeled (E)-β-ionone are detectable after application of d 2-1-deoxy-D-xylulose and d 2-mevalonic acid lactone, respectively. However, (R)-linalool reveals no incorporation of either one of the fed precursors, even though this enantiomer is detectable in the fruit tissue.